Approach of monocarpic senescence control by nitrogen manipulation in mungbean and cowpea: Senescence control by nitrogen manipulation (Journal of the Bangladesh Agricultural University, 2018)
Pods start growing almost at the same time and mature simultaneously in soybean (Glycine max (L.) Merrill) plants. But mungbean (Vigna radiata L. Wilczek) and cowpea (Vigna sinensis Endl.) perform unsynchronized pod maturity. To overcome unsynchronized pod maturity the nitrogen redistribution aspects of mungbean and cowpea were investigated based on the linkage of soybean. Pot experiment was conducted using a nodulating mungbean variety (cv. XANH NINH THUAN) in 2015 and cowpea variety (cv. IT98K-205-8) in 2016 in the vinyl house at Saga University in Japan. During the experiment, nutrient solution was applied by changing nitrogen concentrations to 5, 25 and 100 ppm (control). Mungbean plants provided with low concentration of 5 and 25 ppm of nitrogen supply was not capable to produce continuous pods. Cowpea plants supplied with low concentration of nitrogen was also unable to produce successful pods continuously. Insufficient nitrogen hampered the continuation of pod setting in both the cases, might be due to, all the vegetative stored nitrogen had been utilized for seed development during the vegetative phase before pod setting. In case of 100 ppm nitrogen supply, for both mungbean and cowpea, no senescence and nitrogen remobilization occurred. However, researches showed that soybean typically undergoes the remobilization evidence, i.e., monocarpic senescence, in 100 ppm of nitrogen supply.J.Bangladesh Agril. Univ. 16(3): 386–395, December 2018